Konseling Pastoral bagi Pasangan Kristen yang Mengalami Ketidakhadiran Emosional dalam Pernikahan (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This constructive literature study examines pastoral counseling for Christian couples experiencing emotional absence in marriage. Emotional absence is not identical with open conflict; it appears as reduced responsiveness, muted affect, spiritualized avoidance, and routine coexistence without felt connection. The study aims to formulate an integrative pastoral counseling framework that is theologically accountable and clinically informed. The method is a constructive qualitative literature study using thematic synthesis of studies on marital satisfaction, emotional suppression, perceived partner responsiveness, spiritually integrated psychotherapy, and Christian marital theology published primarily before 2024. The findings indicate that emotional absence should be read as a relational-spiritual rupture involving affect regulation, attachment insecurity, weakened mutual responsiveness, and distorted uses of religious language. The article proposes the REKAT framework: recognition of relational rupture, empathic attunement, covenantal communication, accountable spiritual practices, and tracked follow-up within church care. The framework places Scripture, prayer, confession, forgiveness, and community support within ethical safeguards, especially screening for violence, coercion, and severe mental health risk. The implication is that pastoral counseling can move beyond moral exhortation toward structured accompaniment that rebuilds emotional presence, responsibility, and covenantal intimacy in Christian marriage.